Pembuatan dan Karakterisasi Sensor Amonia Berbasis Bending Fiber Optic - chandra pratiwi; Gandi Sugandi; Junaidi Junaidi (Jurnal Teori dan Aplikasi Fisika, 2018)
This research was approved optical fiber bending sensors with good characterization and variations in the concentration of ammonia solution. This research uses experimental methods in the laboratory. The technique was done by stripping multimode optical fibers (cladding measuring 125 ?m and core 62 ?m) which is exfoliated cladding then replaced by polydimethylsiloxane (PDMS) and bending with the combustion process. The concentration of ammonia solution used in this research varies from 1-10%. Measurement of fiber optic sensors using optical power meter (OPM) with a wavelength of 1310 nm and 1550 nm, and light source (LS) at a frequency of 0 Hz, 270 Hz, 1000 Hz, and 2000 Hz. The result showed that ammonia solution caused instability in light intensity. However, the higher the frequency of light. The lower of the intensity with the difference in intensity produced is very small.Keywords: ammonia, bending, cladding, optical fiber, polydimethylsiloxane (PDMS).